Response of Pigeonpea [Cajanus cajan (L.)] to Foliar Application of Nutrient and Pest Management at Flowering Stage - Meena, S. N.; Patidar, B. K.; Jadon, Chaman; Meena, H. P.; Meena, B. S.; Yadav, R. K.; Yadav, S. L.; Meena, N. L.; Singh, Pratap; Jat, M. L. (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted at Agricultural Research Station, Kota during two consecutive kharif seasons (June to January) of each 2017-18 and 2018-19) to find out suitable combination compatibility between insecticides and foliar nutrients for enhancing productivity and profitability of pigeon pea. The experiment was laid out in RBD design comprising eight treatments with three replication and the variety was ICPL 88039. The soil of experimental field was clay loam in texture, alkaline in reaction, medium in organic carbon, available nitrogen, phosphorus and high in potash. On the basis of pooled analysis, the results revealed that application of RDF+multi-micronutrient (Zn 5.0%, Mn 2.0%, Fe 2.0%, Bo 0.5%, Cu 0.5% and Mo 0.05%) spray @ 2 ml l-1 at 50% flowering+Indoxacarb 15.8 EC @ 375 ml ha-1 at flowering+Dimethoate 30 EC @ 1.0 l ha-1 at 15 days after first spray recorded maximum and significantly higher pods plant-1 (179.0), grain yield (1767 kg ha-1), net return (Rs. 70729 ha-1), B:C ratio (2.96) and minimum pod damage by pod borer (5.25%) and pod fly (5.39%). The treatment RDF+multi-micronutrient spray @ 2 ml l-1 at 50% flowering was next in order of efficacy and other parameters being statistically at par with RDF+1% urea+0.25% ZnSO4+0.25% borax spray at 50% flowering. Whereas, the treatment RDF (20 kg N, 50 kg P2O5, 20 kg S, 25 kg Zn ha-1) was found less effective in comparison to other treatments in all the parameters.